Penjelasan dengan langkah-langkah:
a = 2
b = -1
C = 1
a. 2a + 5b - 3c
= 2(2) + 5(-1) - 3(1)
= 4 - 5 - 3
= -1 - 3
= -4
b.(2)(-1) +(-1)² + 3(2)(1) - (1)
= -2 + 1 + 6 -1
= -1 + 6 - 1
= 5 - 1
= 4
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Penjelasan dengan langkah-langkah:
a = 2
b = -1
C = 1
a. 2a + 5b - 3c
= 2(2) + 5(-1) - 3(1)
= 4 - 5 - 3
= -1 - 3
= -4
b.(2)(-1) +(-1)² + 3(2)(1) - (1)
= -2 + 1 + 6 -1
= -1 + 6 - 1
= 5 - 1
= 4
semoga bermanfaat